(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses how ergonomic conditions can influence the psychosocial aspects of the teaching community, teacher satisfaction with working conditions, and their health and well-being. Due to the physical environment, job demands and technological factors, the work environment and poor management of work activities can lead to negative perceptions of teachers, psychological stress and health problems.